Contemporary approaches to the preparation of metal nanoparticles: methods and mechanistic insights (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Nanoparticles have transformed drug delivery systems to provide new approaches to increase the dissolution, absorption, and targeting properties of drug molecules. They have a nanoscale structure that gives them special characteristics such as high surface area, enhanced membrane permeability and enhanced physicochemical stability in comparison with the traditional drug delivery systems. Such properties render the nanoparticles especially useful in treatment of such complicated illness as cancer, neurodegenerative disorders, and chronic infectious diseases. This review paper focuses on the different ways of synthesizing metal nanoparticles and their pharmaceutical usage, as a way of overcoming the limitations of the conventional methods of delivery. Altogether, nanoparticles are characterized by enhanced stability and bioavailability, reduced toxicity, and a high possibility of benefiting therapeutic performance and safety in nanomedicine.
Keywords: Nanomaterials; Nanoparticles; Nanocomposites; Nanoarchitectures; Nanostructures